Suicide ideation in the university population (Research, Society and Development, 2022)
Analyze whether there are suicidal ideations, identify what the motivations are, and describe the sociodemographic and economic profile of university students. Quantitative, cross-sectional study with undergraduate students from the State University of Minas Gerais – UEMG – Divinópolis in 2020. A Sociodemographic Questionnaire, Suicide Ideation Questionnare (QIS), Beck Scale and Satisfaction with Social Support Scale (ESSS) were used. The chi-square test, Fisher's exact test, calculation of the Odds-Ratio (OR) was performed. Both statistical tests were performed using the Statistical Package for Social Sciences (SPSS) program. 130 university students participated in the study, predominantly female (81.5%), aged between 21 and 25 years (61.5%) and single (78.5%). Of the total sample, 28 (21.53%) were at risk of having suicidal ideation. It was listed that students who live in another city are 1.52 times more likely to have suicidal ideation (CI=0.65-3.55), who have a monthly income less than or equal to the minimum wage increases by 2 times the chances of having suicidal ideation (CI: 0.74-0.53) and claiming to suffer from some mental or behavioral disorder increases by 1.40 times the chances of suicidal ideation (CI=0.60 to 3.25). Knowing the mental characteristics of university students makes it possible to plan joint interventions in the academic community and develop prevention and promotion strategies, reducing suicidal ideation in this public.